Competitive Aggressiveness of Contractors: A Study of Indonesia. (2015) - Setiawan, Harijanto; Erdogan, Bilge; Ogunlana, Stephen O.
Abstract: High level of competition are consideredto be a major challenge for contractors. As such, 'winning the competition' is an important goal for contractors in running their businesses. Contractors need to be aggressive in competition to respond to their competitors' actions and gain competitive advantage against their business rivals for survival and growth. This study aims to clarify the issue of competitive aggressiveness of contractors by identifyingits key factors. Semi-structured interviews were carried out with 19 top managers of contracting companies in Indonesia, in order to explore the concept of contractors' competitive aggressiveness. The qualitative data collected during the interviews were analysed using an inductive thematic analysis method. The analysis resulted in identifying five key factors of contractors'competitive aggressiveness: 1) acting as a problem solver for clients; 2) being different compared to competitors; 3) building and maintaining clients' confidence in the company's trustworthiness and reliability; 4) maintaining good relationships with clients; and 5) positioning on markets that are concerned about quality. Based on these findings, contractors will be able to establish an appropriate strategy to allow them to be aggressive in competition.